Biomethane Production From Food Waste Mixture By Anaerobic Digestion Reactor - Amal Farhah, Hashim (2021)
As the world's population grows and cities grow in size, the food is wasted. Food waste has become a major environmental issue in every country. Food waste is a growing environmental problem that contributes to rising greenhouse gas (GHG) emissions in landfills and negative ecological impacts on society. The current study checks the performance of biomethane production from fruit waste combined with pseudostem bananas in an anaerobic digestion reactor. Biogas is produced through anaerobic digestion in an anaerobic digestion reactor for about four weeks. Fruits and pseudostem bananas waste decomposes in an anaerobic environment, lacking oxygen-producing biogas. In this experiment, the waste fermented in the reactor within 28 days, the pH and volume of biogas per day are needed to monitor and trace the process changes in the reactor, which could lead to a lack of methane production. To produce methane gas, pre-treatment is necessary as some of the waste consists of hemicellulose, which has a double bond structure. Physical treatment was applied in this study to break down the double bond as it effectively increases accessible surface area breaks down lignin-hemicellulose complexes and the usable cellulosic material. The result shown in the study can be used for further research to minimize the food waste production.